Human Nasal Myiasis Caused by Oestrus ovis in the Highlands of Cusco, Peru: Report of a Case and Review of the Literature - P. Hoyer; R. R. Williams; M. Lopez; M. M. Cabada (Case Reports in Infectious Diseases)
Myiasis is the infestation by dipterous larvae. The larvae can infect intact or decaying tissue including the skin or epithelial surfaces of the orbits, nose, and genitourinary and gastrointestinal tracts. We report a case of primary obligatory nasal myiasis by Oestrus ovis in a 56-year-old man from Cusco in Peru. He presented with nasal pruritus, congestion, and sneezing white “cottony” material. The material was identified as O. ovis larvae. A literature review of publications reporting nasal myiasis caused by O. ovis is presented.